2021
DOI: 10.1021/acsenergylett.1c00990
|View full text |Cite
|
Sign up to set email alerts
|

Small Change, Big Difference: Photoelectrochemical Behavior of Au Nanocluster-Sensitized TiO2 Altered by Core Restructuring

Abstract: Ultrasmall gold nanoclusters (Au NCs) have recently gained enormous popularity as a newly emerging light harvester, but many fundamental aspects of their photoelectrochemical behavior are still largely unknown. Unlike traditional photoactive nanoparticles, the NC's core structure, rather than its size, is a key factor that dictates the physical properties of NCs because of a strong quantum confinement effect. Despite this importance, no effort has been made to elucidate the effect of the core structure on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Our group demonstrated this behavior on Au 25 (SR) 18 NCs as a model system . We used a simple chemical etching process to transform Au 25 (SR) 18 to Au 23 (SR) 16 NCs.…”
Section: Core Engineeringmentioning
confidence: 99%
“…Our group demonstrated this behavior on Au 25 (SR) 18 NCs as a model system . We used a simple chemical etching process to transform Au 25 (SR) 18 to Au 23 (SR) 16 NCs.…”
Section: Core Engineeringmentioning
confidence: 99%
“…The 29-fold increase in the photocurrent generation capacity of Au NC-sensitized solar cells since their inception (from 290 μA cm –2 to 8.45 mA cm –2 ) highlights their efficient ability to convert photons into electrical energy. , Furthermore, modulating the electronic structure of Au NCs via an appropriate level of Ag doping has also been shown to be an effective strategy to improve the PCE of MCSSCs . Along with the doping, core restructuring of Au NCs is also a novel strategy to boost the performance of MCSSCs . In addition to Au NCs, stable photocurrent generation from Ag NCs has also been demonstrated, which could open new avenues to put research efforts toward non-Au NC-based sensitizers and help to reduce the overall cost of NC-based devices .…”
Section: Journey Of Thiolated Ncs In Photovoltaicsmentioning
confidence: 99%
“…47 Along with the doping, core restructuring of Au NCs is also a novel strategy to boost the performance of MCSSCs. 48 In addition to Au NCs, stable photocurrent generation from Ag NCs has also been demonstrated, which could open new avenues to put research efforts toward non-Au NC-based sensitizers and help to reduce the overall cost of NC-based devices. 6 However, despite the strides made so far, the PCE of MCSSCs still lags far behind those of their competitors, such as DSSCs and QDSSCs, which is significant because the optimal design of MCSSCs has not yet been obtained.…”
mentioning
confidence: 99%
“…These properties are different from those of conventional Au NPs. Because of these intriguing properties, Au NCs have been applied in a variety of applications such as biomedicine, sensors, catalysis, and light energy conversion systems. , Recently, Au NCs are attracting interest, particularly in electrocatalysis applications, and those studies have shown that Au NCs would be promising materials for the future of electrocatalysis research. …”
Section: Introductionmentioning
confidence: 99%